Respuesta :
-5a²+13ab should be subtracted.
Step-by-step explanation:-
Based on the given conditions, formulate,
[tex]→- {a}^{2} - 4 {a}^{2} + 13ab[/tex]
[tex]→-({a}^{2} - 4 {a}^{2}) + 13ab[/tex]
Taking the coefficients or numbers, we get,
[tex]→(- 1 - 4) {a}^{2} + 13ab[/tex]
[tex]→ - 5 {a}^{2} + 13ab[/tex]
Given :
What should be subtracted from a² – 7ab + 3b² to get – 4a² + 6ab + 3b² ?
Solution :
Let the required expression to be subtracted be x
⇢ a² – 7ab + 3b² – x = – 4a² + 6ab + 3b²
⇢ a² – 7ab + 3b² – (– 4a² + 6ab + 3b²) = x
⇢ a² – 7ab + 3b² + 4a² – 6ab – 3b² = x
Combining the like terms :
⇢ a² + 4a² – 7ab – 6ab + 3b² – 3b² = x
⇢ 5a² – 13ab = x
⇢ x = 5a² – 13ab
Therefore,
5a² – 13ab should be subtracted from a² – 7ab + 3b² to get – 4a² + 6ab + 3b².